BUSINESS INCUBATORS AND ACCELERATORS - INSTRUMENTS IN THE DEVELOPMENT OF THE BUSINESS ENVIRONMENT - CLAUDIA ISAC (Annals of the University of Petrosani: Economics)
The importance of business incubators and accelerators to increase business competitiveness and develop entrepreneurial skills is an important factor in studying their typology and how to implement them at regional level. In this paper, after highlighting some conceptual approaches regarding business incubators and their classification according to different criteria, we have shown the stages of the operational process within a business incubator. At the end of the paper we have shown the context of the implementation of business accelerators as a direct effect of the incubators and to amplify the effects of the technologyinnovation-entrepreneurship synergy.